2021
DOI: 10.3389/fvets.2021.683853
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Broad-Host-Range Lytic Phage SHWT1 Against Multidrug-Resistant Salmonella and Evaluation of Its Therapeutic Efficacy in vitro and in vivo

Abstract: Inappropriate use of antibiotics has accelerated to the emergence of multidrug-resistant bacteria, becoming a major health threat. Moreover, bacterial biofilms contribute to antibiotic resistance and prolonged infections. Bacteriophage (phage) therapy may provide an alternative strategy for controlling multidrug-resistant bacterial infections. In this study, a broad-host-range phage, SHWT1, with lytic activity against multidrug-resistant Salmonella was isolated, characterized and evaluated for the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 63 publications
(99 reference statements)
1
12
0
Order By: Relevance
“…Host range was an essential factor to consider when choosing phages 45. Our results indicated that the isolated bacteriophages had a narrow range of activity. The results of the bacteriophage of Salmonella bacteria in the narrowness of their lytic activity agree with the results of Tao et al 2021 46 in that no lytic activity was observed against the other genera of bacteria. Moreover, results also indicated that pH as well as temperature can influence the efficacy of bacteriophage treatments of pathogenic microorganisms 47 .…”
Section: Bacteriophage Morphology Analysis Using Temsupporting
confidence: 89%
“…Host range was an essential factor to consider when choosing phages 45. Our results indicated that the isolated bacteriophages had a narrow range of activity. The results of the bacteriophage of Salmonella bacteria in the narrowness of their lytic activity agree with the results of Tao et al 2021 46 in that no lytic activity was observed against the other genera of bacteria. Moreover, results also indicated that pH as well as temperature can influence the efficacy of bacteriophage treatments of pathogenic microorganisms 47 .…”
Section: Bacteriophage Morphology Analysis Using Temsupporting
confidence: 89%
“…Phages are generally species-specific or genus-specific ( Hyman and Abedon, 2010 ; Cazares et al, 2021 ). Broad-host range Salmonella phages have been reported in the literature ( Santos et al, 2011 ; Li, M. et al, 2020 ; Tao et al, 2021 ), but phages infecting bacteria from different genera are comparatively rare. It has been reported that phages SFP10 and KIT03 broke the boundary between Salmonella and Escherichia and infected both Salmonella enterica and E. coli O157:H7 ( Park et al, 2012 ; Pham-Khanh et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…8.0 × 10 −10 CFU −1 ·mL·min −1 and 7.0 × 10 −10 CFU −1 ·mL·min −1 , for phages ph001L and ph001T, respectively ( Figure 5 ). These results are of the same order of magnitude as the results reported by [ 85 ] (lytic phage fSPB adsorption rate on Salmonella serovar Paratyphi B, 4.7 × 10 −10 ) and [ 86 ] (adsorption rate of phage 1 = 2.2 × 10 −10 mL·min −1 and adsorption rate of phage 2 = 1.8 × 10 −10 mL·min −1 , onto Salmonella typhi ), one order of magnitude lower than results reported by [ 87 ] (phage PVP-SE1 adsorption rate on Salmonella enterica serovar Enteritidis strain S1400, 1.00 × 10 −9 mL·CFU −1 ·PFU −1 ·h −1 ) and [ 88 ] (phage SHWT1 adsorption rate on Salmonella pullorum SP01, (8.8 ± 0.5) × 10 −9 mL·min −1 ), and two orders of magnitude lower than the results reported by [ 89 ] (phage phi1 adsorption rate onto Salmonella enterica = 1.6 × 10 −8 mL·min −1 ). According to [ 84 ], the adsorption constants in some phages are close to the maximally possible values, viz.…”
Section: Discussionmentioning
confidence: 95%